How creativity differ among rural and urban students: A study - Sharma, Diwaker (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
The objective of this research is to examine, how rural and urban students differ on creativity. Baqar Mehdi test was administered on 400 male and females, randomly selected students  from rural and urban  secondary schools. The result reveals that rural students do the creative work in a very interesting way. Creative potential of both rural male and female students is the same. Overall male students are slightly higher on creativity in comparison to female students.
Keywords: creativity; society; effort; educationist; activities